2012
DOI: 10.2527/jas.2011-4602
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic gene expression and fatty acid composition in subcutaneous adipose tissue depots of Angus steers between 9 and 16 months of age1

Abstract: We have demonstrated that among carcass adipose tissue depots, brisket subcutaneous adipose tissue contains the greatest concentration of MUFA and lowest concentration of SFA. Therefore, we hypothesized that brisket subcutaneous adipose tissue depots would exhibit greater adipogenic gene expression over time than other major subcutaneous adipose tissue depots. Four Angus steers, each at 9, 12, 14, and 16 mo of age, were harvested and fresh subcutaneous adipose tissue samples were collected from over the briske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…We previously demonstrated that fat trim from the brisket contained a higher percentage of MUFA than fat trim from the flank and plate (Smith et al, 2012;Turk & Smith, 2009), and these results were confirmed in this study. Oleic acid is the most abundant fatty acid in ground beef produced from fat and lean trim of commercial beef cattle (reviewed in Adams et al, 2010;Turk & Smith, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We previously demonstrated that fat trim from the brisket contained a higher percentage of MUFA than fat trim from the flank and plate (Smith et al, 2012;Turk & Smith, 2009), and these results were confirmed in this study. Oleic acid is the most abundant fatty acid in ground beef produced from fat and lean trim of commercial beef cattle (reviewed in Adams et al, 2010;Turk & Smith, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…John et al, 1987), although fatty acid composition varies considerably across carcass fat depots and changes with animal age (Smith et al, 2012;Turk & Smith, 2009). Adipose tissue overlying the brisket is unusually high in MUFAs, especially oleic acid, and low in palmitic (16:0) and stearic (18:0) acids (Smith et al, 2012;Turk & Smith, 2009). The plate, which is typically used as raw materials for ground beef production, is intermediate in SFA content, whereas the flank has the highest proportions of SFA (Turk & Smith, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primer sequences of the target genes, PPARG, CEBPA, and a house-keeping gene, GAPDH (glyceraldehyde-3-phosphate dehydrogenase), were designed using Primer Express 2.0 software (Aplied Biosystems, Stockholm, Sweden).The primer sequences were: PPARG, forward 5′-CGACCAACTGAACCCAGA-3′ and reverse 5′-AGCGGGAAGGACTTTATGT-3′; CEBPΑ, forward 5′-CCCGATAAAGCCAGCACT-3′ and reverse 5′-CCACCTTCACGCAGAACA-3′; GAPDH, forward 5′-GGTGATGCTGGTGCTGAGT-3′ and reverse 5′-ATGATGACCCTCTTGGCG-3′. Quantitative real-time PCR (qPCR) was used to analyse the expression of PPARG (accession number: BC116098.1), CEBPA (accession number: BC149006.1), and the housekeeping gene, GAPDH (accession number: NM_001034034.1), which was used as an endogenous control (Smith et al, 2012). The qPCR reaction system had the following parameters: 1 μl of the cDNA template, 10 μl of 2 × SYBR real-time PCR premixture PR7002, (BioTeke, Beijing, China), 0.4 μl of the forward primer, 0.4 μl of reverse primer, and 8.2 μl to 20 μl of ddH 2 O.…”
Section: Total Rna Extract and Relative Quantitative Real-time Polymementioning
confidence: 99%
“…Unfortunately, knowledge of factors controlling these processes and how production practices influence such factors is limited in cattle, especially concerning mechanisms that control the timing and extent of depot development. 88 Consequently, it has proven difficult to devise strategies that enhance marbling and simultaneously limit adipose tissue accretion in undesirable depots that negatively impact feed efficiency and yield grade in livestock.…”
Section: Gene Expression Studies In Bovine Intramuscular and Subcutanmentioning
confidence: 99%